2021
DOI: 10.22624/aims/abmic2021p9
|View full text |Cite
|
Sign up to set email alerts
|

Application of Artificial Intelligence (AI) Approach to African Real Estate Market Analysis Opportunities and Challenges

Abstract: The information on the real estate market is fast growing and becoming more complex to analyse. Therefore there is a need for reliable real estate market analysis for an informed and handsome investment decision making. The study examines the opportunities and challenges of using artificial intelligence (AI) approaches to analyse quantitative / data on the Africa real estate market. A systematic review of the literature was conducted. The study found some opportunities characterised by the usage of AI tools to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…Furthermore, the application of big data analytics in marketing offers substantial potential for growth and improvement. Studies have shown that big data analytics can provide valuable insights in various industries, including airlines (Odunfa et al, 2021), real estate (Akhmetova & Nevskaya, 2020), and human resources management (Wamba et al, 2017). The use of predictive analytics, coupled with big data, can lead to better decision-making processes and improved performance in marketing strategies.…”
Section: Challenges and Opportunities For Using Predictive Analytics ...mentioning
confidence: 99%
“…Furthermore, the application of big data analytics in marketing offers substantial potential for growth and improvement. Studies have shown that big data analytics can provide valuable insights in various industries, including airlines (Odunfa et al, 2021), real estate (Akhmetova & Nevskaya, 2020), and human resources management (Wamba et al, 2017). The use of predictive analytics, coupled with big data, can lead to better decision-making processes and improved performance in marketing strategies.…”
Section: Challenges and Opportunities For Using Predictive Analytics ...mentioning
confidence: 99%
“…Despite the potential benefits, African businesses face several challenges and constraints in adopting AI. Resource limitations, including access to funding and technological infrastructure, have been identified as significant barriers to AI adoption (Odunfa et al, 2021). Moreover, skill gaps in AI expertise pose a challenge, as there is a shortage of professionals with the necessary AI skills in the African job market (Schoeman & Seymour, n.d.).…”
Section: African Trends In Ai Adoptionmentioning
confidence: 99%